Prevalence and clinical characterization of oral clefts in patients with chromosome trisomy 18 - Nadini Cristina Marins Martinez; Sheila Tamanini de Almeida; Rafael Fabiano Machado Rosa; Paulo Ricardo Gazzola Zen (Sociedade de Pediatria de São Paulo, 2024)
ABSTRACT Objective: To verify the prevalence and perform the clinical characterization of oral clefts in a sample of patients with trisomy of chromosome 18 in Southern Brazil. Methods: This was a retrospective cross-sectional study, performed in a reference clinical genetic service in Southern Brazil. The initial sample consisted of 77 patients diagnosed in the neonatal period with trisomy 18 treated at the Clinical Genetics Service of a referral hospital at Federal University of Health Sciences of Porto Alegre (UFCSPA). The patients' diagnosis was confirmed by karyotype and care was provided during their stay in the intensive care unit (ICU) of the hospital that is a reference in Southern Brazil for care for malformed patients. The period covered was from 1975 to 2020. Results: During the study period, 77 patients diagnosed with trisomy 18 were treated, most of them in the ICU. Of these, 13 individuals were excluded due to incomplete data. The final sample consisted of 64 patients with an average age of 2.4 years of life, ranging from one day to 16 years old, the majority of whom were female. Regarding face dysmorphisms identified in the sample, three (4,68%) patients had cleft lip and two (3,11%) had cleft lip and palate. Conclusions: This study contributed to the recognition of the characteristics and prevalence of oral clefts in individuals with trisomy 18 in a sample of patients from Southern Brazil. In addition, we described the clinical alterations found in patients with oral clefts, as well as other associated comorbidities, such as cardiac, neurological and pulmonary comorbidities, as well as cranial and facial dysmorphisms.